Synthesis and Fungicidal Activities of 1-(5-Methylisoxazoyl-4-carbonyl)-4-arylsulfonyl Thiosemicarbazides - Ye, Dong-Ju (Asian Journal of Chemistry, 2010)
1-(5-Methylisoxazoyl-4-carbonyl)-4-arylsulfonyl thiosemicarbazides, which were prepared by treatment of arylsulfonyl hydrazine with 5-methyl-isoxazole-4-carbonyl isothiocyanate in good yields. The structures of all compounds were confirmed by 1H NMR, MS and elemental analyses. The preliminary bioassays indicated that some compounds are comparable to the commercial fungicides. Some of these compounds also exhibit moderate fungicidal activities